Auditors' Professional Integrity and Skepticism Towards Audit Quality: (A Case Study At The Bandung City Inspectorate) - Muhammad Mulia Ramadhan (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze and empirically examine the influence of auditor competence, professional integrity, and professional skepticism on audit quality in the public sector, with a specific focus on internal auditors at the Bandung City Regional Inspectorate. Research Method: The study adopts an associative quantitative research design. Data were collected from all internal auditors at the Bandung City Regional Inspectorate, totaling 30 respondents, using a structured questionnaire. The entire population was included as research subjects through a census approach. Data analysis was conducted using multiple regression techniques to test the individual effects of auditor competence, integrity, and professional skepticism on audit quality. Results and Discussion: The results indicate that auditor competence has a positive and significant influence on audit quality, suggesting that greater knowledge, skills, and experience contribute to better audit outcomes. Auditor integrity also has a significant positive effect on audit quality, underscoring the importance of ethical commitment and objectivity in audit work. Furthermore, professional skepticism positively influences audit quality, confirming that a critical, questioning mindset enhances the reliability and credibility of audit results. These findings collectively demonstrate that auditors' behavioral and professional attributes play a crucial role in determining audit quality. Implications: The study offers practical implications for public-sector audit institutions by emphasizing the need to strengthen auditors' competence, integrity, and professional skepticism through continuous training, ethical development, and a supportive organizational culture to improve audit quality and accountability.